2009
DOI: 10.1093/hmg/ddp291
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect roles of RECQL4 in modulating base excision repair capacity

Abstract: RECQL4 is a human RecQ helicase which is mutated in approximately two-thirds of individuals with Rothmund-Thomson syndrome (RTS), a disease characterized at the cellular level by chromosomal instability. BLM and WRN are also human RecQ helicases, which are mutated in Bloom and Werner's syndrome, respectively, and associated with chromosomal instability as well as premature aging. Here we show that primary RTS and RECQL4 siRNA knockdown human fibroblasts accumulate more H(2)O(2)-induced DNA strand breaks than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 69 publications
3
89
0
2
Order By: Relevance
“…Oxidative Stress and UV Exposure Increases Nuclear RPS3-RECQL4 Interaction in a Dose-dependent Manner-The helicase domain of RECQL4 has been shown to be important for various DNA repair functions (13)(14)(15), and this domain is frequently mutated in RTS, Baller-Gerald Syndrome, and RAPA-DILLINO syndrome patients (23). RTS patients are more prone to osteoskeletal deformities and osteosarcoma (23), and some studies have shown them to have increased sensitivity to UV (15) and oxidative stress (14,33).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Oxidative Stress and UV Exposure Increases Nuclear RPS3-RECQL4 Interaction in a Dose-dependent Manner-The helicase domain of RECQL4 has been shown to be important for various DNA repair functions (13)(14)(15), and this domain is frequently mutated in RTS, Baller-Gerald Syndrome, and RAPA-DILLINO syndrome patients (23). RTS patients are more prone to osteoskeletal deformities and osteosarcoma (23), and some studies have shown them to have increased sensitivity to UV (15) and oxidative stress (14,33).…”
Section: Resultsmentioning
confidence: 99%
“…RTS patients are more prone to osteoskeletal deformities and osteosarcoma (23), and some studies have shown them to have increased sensitivity to UV (15) and oxidative stress (14,33). RPS3 is also important for the progression of osteosarcoma (28).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations